Critically evaluating the special international relationship between the UN Security Council and the International Criminal Court (ICC) - Sheraz Ibrahim (QALAAI ZANIST SCIENTIFIC JOURNAL, 2021)
This paper will critically evaluate the relationship between UN security council and the ICC regarding the empowerment of the International Criminal Court and its Prosecutors by the Security Council’s use of power under Article 13(b) of the Rome Statute to refer a situation to the ICC and the use of Article 16 to defer investigations and prosecutions. The paper will neatly assess the relationship between the two international bodies. Focusing on the Security Council’s intervention in judicial proceedings as apolitical organ requires some explanation. The purpose for the intervention and the relationship under the primary responsibility of the Security Council for the maintenance of peace and security will be explored to evaluate the effectiveness of the relationship in maintaining peace and security. Analysis will be put on the international relationship in respecting each other’s status and mandate to deliver its original aim under international law. Using the Rome Statue to examine the legal parameters of this relationship in addition to any other consideration to define the relationship and the impact of the two institutions.